PROSTITUSI ONLINE DAN EKSISTENSI KEKUASAAN PEMERINTAH - Teza Yudha; Wahyu Utamidewi; Sopyan Resmana Adiarsa (Jurnal Sosial Soedirman, 2018)
Information globalization has placed Indonesia as part of the world's information society, requiring the establishment of arrangements for the management of information and electronic transactions at the national level. In line with these developments, the internet has changed everything, from the way people think, communicate, connect, work, shop, to the pattern of people in making love. Sexual access can now be easily obtained, from contemporary pornographic content to online prostitution, produced and distributed massively and very quickly on the internet.The idea of sexuality that used to be taboo now obtains a space to discuss. Through the internet, sexuality is used as a recreational arena and a biological necessity as an essential outlet for desire and lust. As Foucault shows that sexuality is not merely a biological drive, but is a form of behavior and thoughts that are subordinated by power relations that are carried out for the purpose other objectives outside the interests of sexuality itself. It is this power that should be used as "social control", legal decisions, to government regulation of sexuality freedom on the internet. The purpose of this study is to find out how the reality of online prostitution is now growing and its relation to government arrangements. This study uses a virtual ethnographic method. The results showed that the Internet became a medium of online prostitution development that increases rapidly so that almost abandon the government power to regulate it.